KETAKUTAN DAN RESILIENSI DALAM JALAN TAK ADA UJUNG KARYA MOCHTAR LUBIS (FEAR AND RESILIENCE IN JALAN TAK ADA UJUNG BY MOCHTAR LUBIS) - Purba, Rosma Indriana; Banjarnahor, Joseph Casey Diego (Universitas Lambung Mangkurat, 2025)
AbstractFear and Resilience in Jalan Tak Ada Ujung by Mochtar Lubis. Fear is a fundamental human emotion that arises in situations of threat and uncertainty. Jalan Tak Ada Ujung, a novel written by Mochtar Lubis represents the complexity of this emotion through the characters of Guru Isa and Hazil who live under the repressive pressure of the colonial era. This study aims to examine the psychological transformation of the two characters through the lens of literary psychology, with a focus on the resilience mechanisms formed from traumatic experiences. Using a qualitative descriptive approach and thematic analysis of the characters' narratives, this study finds that fear, which was initially debilitating, develops into an internal strength through cognitive restructuring and the search for meaning, in accordance with the post-traumatic growth theory which explains how individuals can experience positive psychological development after going through trauma. This finding affirms that literature is not only a medium for representing emotions, but also a space for reflection on the human capacity to grow from suffering.Keywords: fear, resilience, literary psychology, trauma, Jalan Tak Ada UjungAbstrakKetakutan dan Resiliensi Dalam Jalan Tak Ada Ujung Karya Mochtar Lubis. Ketakutan merupakan emosi fundamental manusia yang muncul dalam situasi ancaman dan ketidakpastian. Novel Jalan Tak Ada Ujung karya Mochtar Lubis merepresentasikan kompleksitas emosi ini melalui tokoh Guru Isa dan Hazil yang hidup dalam tekanan represif masa penjajahan. Penelitian ini bertujuan mengkaji transformasi psikologis kedua tokoh tersebut melalui lensa psikologi sastra, dengan fokus pada mekanisme resiliensi yang terbentuk dari pengalaman traumatis. Menggunakan pendekatan deskriptif kualitatif dan analisis tematik terhadap narasi tokoh, kajian ini menemukan bahwa ketakutan yang semula melemahkan berkembang menjadi kekuatan internal melalui restrukturisasi kognitif dan pencarian makna sesuai dengan teori post-traumatic growth yang menjelaskan bagaimana individu dapat mengalami perkembangan psikologis positif setelah melewati trauma. Temuan ini menegaskan bahwa sastra bukan hanya medium representasi emosi, tetapi juga ruang refleksi atas kapasitas manusia untuk bertumbuh dari penderitaan.Kata-kata kunci: Ketakutan, resiliensi, psikologi sastra, trauma, Jalan Tak Ada Ujung